2-Chloro-5-({[5-(4-methoxyphenyl)-1,3,4-oxadiazol-2-yl]sulfanyl}methyl)pyridine - Ji, Hao (International Union of Crystallography, 2011)
In the title compound, C15H12ClN3O2S, the central oxadiazole ring forms dihedral angles of 7.72 (14) and 69.86 (12)° with the benzene and pyridine rings, respectively. The crystal packing is governed only by van der Waals interactions.